2004
DOI: 10.1076/ceyr.28.1.17.23488
|View full text |Cite
|
Sign up to set email alerts
|

Peroxynitrite-induced apoptosis in photoreceptor cells

Abstract: These results show that peroxynitrite induces apoptosis in photoreceptor cells and that such retinal damage appears to be mediated by caspase-3. The apoptotic process can be minimized by peroxynitrite scavenger urate, as well as by the caspase inhibitor Z-VAD-fmk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 13 publications
1
11
0
Order By: Relevance
“…We also showed that in EAU, mitochondrial oxidative stress occurs before macrophage or other inflammatory cellular infiltration [7]. These findings support previous studies from our laboratory that determined that peroxynitrite-mediated nitration of photoreceptor mitochondrial proteins, as well as the presence of reactive oxidants and peroxynitrite, occurs in mitochondrial photoreceptors during early EAU [17, 18]. Oxidative stress appears to target the mitochondria as the original site of inflammation and thus damaged or altered mtDNA is a major target for oxidative damage.…”
Section: Photoreceptor Mitochondrial Oxidative Stresssupporting
confidence: 89%
See 1 more Smart Citation
“…We also showed that in EAU, mitochondrial oxidative stress occurs before macrophage or other inflammatory cellular infiltration [7]. These findings support previous studies from our laboratory that determined that peroxynitrite-mediated nitration of photoreceptor mitochondrial proteins, as well as the presence of reactive oxidants and peroxynitrite, occurs in mitochondrial photoreceptors during early EAU [17, 18]. Oxidative stress appears to target the mitochondria as the original site of inflammation and thus damaged or altered mtDNA is a major target for oxidative damage.…”
Section: Photoreceptor Mitochondrial Oxidative Stresssupporting
confidence: 89%
“…Prior to leukocyte infiltration during early EAU, selective peroxynitrite-mediated nitration of photoreceptor mitochondrial proteins occurs [17]. Our studies show that in the early stages of EAU, mitochondria are the major source of ONOO − , and mitochondrial proteins are the prime target for inactivation, further implicating photoreceptor mitochondria as initiators of the proinflammatory response in early EAU [6].…”
Section: Introductionmentioning
confidence: 91%
“…We further evaluated the protective effect of propofol on peroxynitrite mediated apoptosis as it occurs in photoreceptors cells (Ito, S., 2004) and in cerebral vascular muscle cells (Li, J., 2003). Traditionally, necrosis was believed to be the predominant mechanism of astrocyte death in CNS injury models.…”
Section: Discussionmentioning
confidence: 99%
“…Macrophages and T cells typically infiltrate the retina in the early stages of EAU (days 11-12 after immunization). However, in day 5 after immunization, studies have shown peroxynitrite-mediated nitration of photoreceptor mitochondrial proteins [16], leading to mitochondria dysregulation and cell death [17]. Lipofuscins are thought to represent the breakdown product of various retinal proteins as a result of oxidative damage which is thought to play a role in uveitic diseases [18].…”
Section: Introductionmentioning
confidence: 99%